Sex-divergent effects of hindbrain GLP-1-producing neuron activation in rats - Lopez-Ferreras, Lorena; Asker, Mohammed; Krieger, Jean-Philippe; Skibicka, Karolina Patrycja (Frontiers in Neuroscience, 2023)
Glucagon-like peptide 1 (GLP-1) analogues represent a new class of weight loss medication, which has recently exponentially grown in popularity. GLP-1 is produced in the intestinal L cells in response to macronutrient intake, but it is also produced in the brain in a subset of neurons in the nucleus of the solitary tract (NTS). Exogenously delivered GLP-1 analogues reduce food intake and food motivated behavior in male and female rats, with some sex divergence of these effects in specific brain sites. These analogues potentially target GLP-1 receptors endogenously supplied by gut, but also, brain-produced GLP-1. The function of the NTS GLP-1-producing neurons [Gcg neurons], is still relatively unknown in the rat. Moreover, even less is understood about the function of these neurons in females.We have recently developed a transgenic rat which expresses Cre under the Gcg promoter. Here we interrogate this new animal model with optogenetics and chemogenetics to determine whether activation of the NTS GLP-1 neurons affects ingestive and motivated behavior, in male and female rats.Optogenetic activation of the NTS Gcg neurons robustly reduced chow intake in both male and female rats. Interestingly, motivated behavior for a sucrose reward was reduced exclusively in females. To ensure that this unexpected sex difference was not activation method specific, we next virally introduced excitatory DREADD receptors into the Gcg neurons and investigated the effect of chemogenetic activation of these neurons on ingestive and motivated behavior. Even upon chemogenetic activation female rats reduced their motivation to obtain the sucrose reward, yet no effect on this behavior was observed in males.Our results show that activation of hindbrain Gcg neurons is sufficient to reduce food intake in both sexes. In females, but not males, Gcg neuron activation alone is also sufficient to reduce motivated behavior for sucrose. Thus, there is a sex difference in the ability of GLP-1producing neuron activation to control motivated behavior for food.